Polarized Worlds and Contextual Creativity in Creative Industries: The Case of Creation Processes in the Perfume Industry - Paris, Thomas; Lang, Gerald; Massé, David (Management international / International Management / Gestiòn Internacional, 2020)
Providing different creative approaches and involving different players, opposite worlds co-exist within a creative industry. Nevertheless, surprising collaborations occur between these worlds. Based on an in-depth exploratory study in the perfume industry, this paper analyzes how designers can create differently in such opposite worlds. In addition to the social and conventional dimensions, we show that these opposite worlds are structured by differences in industry organization, distribution systems and creation processes. We propose the notion of contextual creativity: it means that creators’ creativity is embedded in a specific context. We identify a specific kind of collaboration between opposite worlds: creative symbiosis.